2021
DOI: 10.1186/s13287-021-02201-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of BMMSC treatment on lung tissue degeneration in elderly macaques

Abstract: Background Age-associated lung tissue degeneration is a risk factor for lung injury and exacerbated lung disease. It is also the main risk factor for chronic lung diseases (such as COPD, idiopathic pulmonary fibrosis, cancer, among others). So, it is particularly important to find new anti-aging treatments. Methods We systematically screened and evaluated elderly senile multiple organ dysfunction macaque models to determine whether BMMSCs inhibited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…However, further study is needed to elucidate the exact mechanism through which BMSCs inhibit apoptosis or reduce alveolar damage. BMSCs transplanted via the tail vein can accumulate in the pulmonary circulatory system and participate in the treatment of lung diseases [ 57 , 58 ]. The local expression of SDF-1 increases after lung tissue damage, and BMSCs overexpressing CXCR4 can be recruited to lung tissue much more easily via the SDF‐1/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, further study is needed to elucidate the exact mechanism through which BMSCs inhibit apoptosis or reduce alveolar damage. BMSCs transplanted via the tail vein can accumulate in the pulmonary circulatory system and participate in the treatment of lung diseases [ 57 , 58 ]. The local expression of SDF-1 increases after lung tissue damage, and BMSCs overexpressing CXCR4 can be recruited to lung tissue much more easily via the SDF‐1/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, bmMSCs were obtained from porcine material and cultured. Mesenchymal stem cells are the most frequently used cell type for application in regenerative medicine [ 26 ]. Numerous studies have shown the valuable effects of MSC-based therapies for the treatment of pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and growth characteristics of P0 to P4 BMMSCs were observed. P4 BMMSCs were used for flow cytometric analysis to determine the proportion of BMMSC surface antigens and for adipogenic, osteogenic, and chondrogenic induction and differentiation experiments based on methods published previously by our research group [13][14][15][16][17].…”
Section: Preparation Of Bmmscsmentioning
confidence: 99%